Suplementação com ferro injetável em cordeiros infectados experimentalmente por Haemonchus contortus - Casanova, Valeska Paula (2016)
Gastrointestinal worms are the main obstacle in the production of sheep. The helminth Haemonchus contortus is the species that most parasites sheep in Brazil. It is located in the abomaso of the host and has a habit of blood feeding. Considering clinical signs, the animals present anemia and hypoproteinemia, which reduces the productivity of animals; it can lead to death and causes serious damage to the activity. Iron supplementation in parasitized sheep assists in the hematopoietic process, although further studies are needed to assess the iron metabolism in such animals. Given the above, the following study aimed to evaluate the effects of injectable iron supplementation in sheep experimentally infected with Haemonchus contortusTwenty-four lambs have been used, divided into four groups, being Group 1 - uninfected animals, Group 2 - animals infected with 10000 third stage larvae of H. contortus and treated with three doses of 20mg/kg of body weight of dextran iron intramuscularly, one dose every seven days, Group 3 - non-infected animals and treated with three doses of 20mg/kg body weight iron dextran intramuscularly, one dose every seven days, and Group 4 - animals infected with 10000 third stage larvae of H. contortus. The experiment has lasted 21 days. Blood samples were collected on days 10 (D10), 17 (D17), 24 (D24), and 31 (D31) after parasitic infection to assess the metabolism of iron (ferritin, transferrin, Serum Iron, saturation index to transferrin, Iron Connection Total Capacity, and Spinal Cord Iron stocks) and erythrocyte (red blood cell count, Hematocrit, hemoglobin, reticulocytes, mean corpuscular hemoglobin concentration). Samples of feces for measuring the number of eggs per gram of feces (EPG) have been obtained at the same experimental time. OPG values were positive in Groups 2 and 4. Regarding hematological indices, groups of animals infected and treated with iron had higher values of hematocrit and hemoglobin compared to the group of animals infected and not treated with iron. The results showed that the spinal cord iron stocks were greater in the groups supplemented with iron. Sheep infected with H. contortus presented exhaustion of iron spinal cord reserves, thus the use of injectable iron aids in maintaining the stock and makes the mineral available for erythropoiesis by improving the organic response of animals against infection.